Hyaluronic acid controls the uptake pathway and intracellular trafficking of an octaarginine-modified gene vector in CD44 positive- and CD44 negative-cells. (June 2015) - Yamada, Yuma; Hashida, Masahiro; Harashima, Hideyoshi
Abstract: The cellular uptake pathway for a gene vector is an important factor in transgene expression. We previously constructed an original gene vector, multifunctional envelope-type nano device (MEND). The use of octaarginine (R8), a cell-penetrating peptide dramatically enhanced the transfection activity of the MEND since efficient cellular uptake via macropinocytosis, while the R8 should overcome its poor cell selectivity. Here we prepared an R8-MEND equipped with GALA (a peptide for endosomal escape) (R8/GALA-MEND) coated with hyaluronic acid (HA) (HA-R8/GALA-MEND), a natural ligand for cancer cells overexpressing CD44. We investigated the cellular uptake pathway of the HA-R8/GALA-MEND and the R8/GALA-MEND using HCT116 cells overexpressing CD44. Both carriers were taken up by cells mainly via macropinocytosis, whereas only the HA-R8/GALA-MEND was partially internalized into cells via a CD44-mediated pathway. Investigation of transgene expression showed that the HA-R8/GALA-MEND had a high transfection activity in HCT116 cells via both macropinocytotic and CD44-mediated pathways. On the other hand, the value for the HA-R8/GALA-MEND was significantly decreased compared with the value for the R8/GALA-MEND in NIH3T3 cells (CD44-negative cells). These findings indicate that the HA-coating controls the intracellular pathway for R8-modified nanocarriers, and that a CD44-mediated pathway is an important route for transgene expression.